2019
DOI: 10.4136/ambi-agua.2266
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and hematological biomarkers in tambaqui Colossoma macropomum (Cuvier, 1816) from an environmental protection area of Maranhão, Brazil

Abstract: This study analyzed histopathological (gill lesions) and hematological (erythrocyte abnormalities) changes in tambaqui (Colossoma macropomum) in order to evaluate the water quality of fish farms in the Environmental Protection Area (EPA) of Maracanã, Maranhão, Brazil. Specimens of tambaqui were captured in two areas of EPA: A1) Serena Lagoon, and A2) River Ambude, in two seasonal periods, rainy and dry. For the hematological analyses, slides were made from the blood smear collected from the branchial arch of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The tambaqui species is considered a biological model due to its resilience to environmental changes (Val & Oliveira 2021). It has been pointed out as a bioindicator of environmental pollution and used in several toxicological studies, such as the assessment of genotoxic and hematological parameters (Carvalho-Neta et al 2015), and branchial lesions and erythrocytic abnormalities (Castro et al 2019), both using individuals from an environmental protection area from the Upaon-Açu island, State of Maranhão, northeastern Brazil. Regarding agricultural defensives specifically, studies carried out with tambaqui by Cunha et al (2018) indicated alteration and damage of nuclear erythrocytes in the gills and liver of tambaqui exposed to pesticides such as Deltamethrin.…”
Section: Discussionmentioning
confidence: 99%
“…The tambaqui species is considered a biological model due to its resilience to environmental changes (Val & Oliveira 2021). It has been pointed out as a bioindicator of environmental pollution and used in several toxicological studies, such as the assessment of genotoxic and hematological parameters (Carvalho-Neta et al 2015), and branchial lesions and erythrocytic abnormalities (Castro et al 2019), both using individuals from an environmental protection area from the Upaon-Açu island, State of Maranhão, northeastern Brazil. Regarding agricultural defensives specifically, studies carried out with tambaqui by Cunha et al (2018) indicated alteration and damage of nuclear erythrocytes in the gills and liver of tambaqui exposed to pesticides such as Deltamethrin.…”
Section: Discussionmentioning
confidence: 99%
“…However, possibly due to the experimental conditions, they Magna Scientia UCEVA 2(1), 2022 underwent and to the process of parasitic infestation, they were unable to achieve optimal growth for a suitable cropping system. By other side, hepatic tissue plays a vital role in metabolism such as synthesis, secretion, storage, biotransformation and metabolism [26]. Histopathological changes such as vacuolization of hepatocytes, glycogen depletion, and inflammation, alterations in the shape of sinusoid vessels and neoplasms in the liver of fish are efficient biomarkers that indicate the previous exposure of the animal to stressors present in the environment [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The diverse genotoxic alterations found in the blood cells of aquatic organisms, such as sh, may indicate a compromised physiological and biochemical state (Adeyemo et al 2009). According to Castro et al (2019), the abnormalities found in sh erythrocytes may be related to cytotoxicity processes, in uences on cell Division, and genotoxicity or mutagenicity. The micronucleus test has the function of detecting structural and numerical chromosomal alterations, an important phase that helps in the study of mutagenic substances (Heddle et al 1983).…”
Section: Micronucleus (Mn) Andmentioning
confidence: 99%